Refino de grão na transformação austenítica em aço rolamento previamente conformado a frio - Martins, Ivan Augusto (Universidade Federal de São Carlos, 2012)
In this work is presented the characteristics of the steel C80U Modified, usually applied for bearing components produced through cold forming, as evaluated the influence of prior cold work on the microstructure after heat treatment by quenching and tempering. Starting from spheroidized carbides annealed structure, samples of strip steel were previously cold-rolled to different deformation degrees. The thickness reduction was based on the equivalent strain, calculated by numerical simulation in reference of a real cold formed part. These samples were quenched and tempered, and then the austenitic grain size for each different conditions of prior cold work was evaluated. By X-ray diffraction techniques the fractions of retained austenite for each degree of prior cold work were measured. Mechanical and metallurgical analysis were also carried out in rerolled strips as annealed in delivery condition, in order to characterize the fundamental properties related to drawing process.
Grain refinement in austenitic transformation for a bearing steel prior cold worked
Keywords: Aço; Aço C80U modificado; Estampagem (trabalhos em metal); Deformação preliminar a frio; Refino de grão; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA